2020
DOI: 10.36227/techrxiv.12363572.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Asymptotic Reverse Waterfilling Algorithm of NRDF for Certain Classes of Vector Gauss-Markov Processes

Abstract: <div>In this paper, we revisit the asymptotic reverse-waterfilling characterization of the nonanticipative rate distortion</div><div>function (NRDF) derived for a time-invariant multidimensional Gauss-Markov processes with mean-squared error (MSE) distortion in [1]. We show that for certain classes of time-invariant multidimensional Gauss-Markov processes, the specific characterization behaves as a reverse-waterfilling algorithm obtained in matrix form ensuring that the numerical approach of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…(2) If in (44), we take µ Q,i = 0, for some i, then for that i, it can be easily shown that our solution will recover as a special case, the reverse-waterfilling algorithm obtained for the "fully observable" time-invariant multidimensional Gauss-Markov processes subject to a MSE distortion constraint derived in [24,Proposition 1].…”
Section: New Results For Jointly Gaussian Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) If in (44), we take µ Q,i = 0, for some i, then for that i, it can be easily shown that our solution will recover as a special case, the reverse-waterfilling algorithm obtained for the "fully observable" time-invariant multidimensional Gauss-Markov processes subject to a MSE distortion constraint derived in [24,Proposition 1].…”
Section: New Results For Jointly Gaussian Processesmentioning
confidence: 99%
“…(3) Due to the pay-off in (44) that is greater than the corresponding one obtained for fully observable processes (only the first term appears in that case), the reverse-waterfilling solution of Theorem 5 will always be an upper bound on the reverse-waterfilling obtained for fully observable multivariate processes in [24,Proposition 1] for the rate-distortion region that these are both defined.…”
Section: New Results For Jointly Gaussian Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…where θ * > 0, µ Υ,i 2µ A 2 ,i µΣ ,i > 0 5 and D > D min [0,∞] . Proof: When Σ 0 the derivation follows using similar steps of the derivation of [17,Theorem 2] and we omit it. However, if for instance in Proposition 3, (i), Σ 0 we use a standard continuity argument, that is, there exists a δ > 0 such that Σ = Σ + I p is nonsingular for all ∈ (0, δ) (see, e.g., [36,Theorem 2.9]).…”
Section: Complete Characterization and Optimal Computational Methods: Infinite Time Horizonmentioning
confidence: 99%
“…Another important question has to do with the conditions that are needed to ensure (strict) feasibility of the optimization problem in both finite and infinite time horizon. Equally important questions include the derivation of optimal or suboptimal (numerical or analytical) solutions for this problem for both scalar or beyond scalar processes as well as the analysis of the problem for high dimensional systems that necessitates scalable optimization algorithms (an issue already known from the analysis of [17]).…”
Section: Introductionmentioning
confidence: 99%